Quantifying cardinal temperature and hydro time germination of Cuminum cyminum seeds - Ali Ebadi; ghasem parmoon; Fatme Ahmadnia; Mohamad Godarzy; S. Ghahremani (علوم و فناوری بذر ایران, 2020)
In order to quantifying cardinal temperature and hydro time germination of Cuminum cyminum seeds, an experiment was conducted as completely randomized design with three replications in laboratory of Faculty of Agriculture and Natural Resources of University of Mohaghegh Ardabili in 2017. Experimental treatments were included: temperatures as, 0, 5, 10, 15, 20, 25, 30, 35 and 40 ˚C and osmotic potential as 0, -0.2, -0.4, -0.6, -0.8, -1 and -1.2 MPa. Quantifying of cardinal temperature for germination fraction of 10, 50 and 90 % were evaluated from four models as: beta, modified beta, dent-like and segmented. In this study, RMSE and R2 and AICc were used for comparison between models. Result indicted that beta model showed better responses description for germination rate of Cuminum cyminum to temperature compared with others models. However basic temperature of Cuminum cyminum was between 0.7 to 0.9 ˚C, optimum temperature about 20 to 21 ˚C and maximum temperature was 35 ˚C. In addition based on hydro time models results, θH and Ψb(50) of Cuminum cyminum were estimated 97.5 and -0.46 MPa respectively.